Catching a case : inequality and fear in New York City's child welfare system - Lee, Tina, 1976- (Rutgers University Press, 2016)
Based on extensive research into the child welfare system in New York City, Catching a Case reveals that, in the face of draconian budget cuts and a political climate that blames the poor for their own poverty, child welfare practices have become punitive, focused on removing children from their families and on parental compliance with rules. Rather than provide needed help for family problems, case workers often hold parents to standards almost impossible for working-class and poor parents to meet.